Pre-Concentration and Determination of Tetracyclines Antibiotics Residues in Water Samples Using RGO/Fe3O4 Nanocomposite as Extraction Sorbent - Ungku Amirul Arif Ungku Abdullah; Nor Suhaila Mohamad Hanapi; Wan Nazihah Wan Ibrahim; Nursyamsyila Mat Hadzir; Nurzaimah Zaini; Ahmad Lutfi Anis; Noorfatimah Yahaya (Indonesian Journal of Chemistry, 2021)
Existing methods used in tracing Tetracyclines' antibiotics (TCAs) residues which pose serious environmental problems, consume high amounts of organic solvents, are time-consuming, and are relatively expensive. A simple and effective magnetic solid-phase extraction (MSPE) based on reduced graphene oxide/magnetite (RGO/Fe3O4) nanocomposite sorbent was successfully developed for preconcentration and extraction of TCAs residues from water samples. The analytes were determined by high-performance liquid chromatography with a diode-array detector (HPLC-DAD). The synthesized nanocomposite was characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), and field emission scanning electron microscopy (FESEM). Sample pH, amount of adsorbent, sample volume, extraction time, desorption time, and desorption solvent were evaluated and optimized. Under optimized conditions, the method demonstrated good linearity over the concentration range of 0.05–1.0 mg L–1 with the coefficient of determination (R2) ≥ 0.9978. Limit of detection (LOD) and limit of quantification (LOQ) were 0.006–0.011 mg L–1 and 0.019–0.036 mg L–1, respectively. The accuracy and precision of the developed method were proven by good analyte recovery (89.77–106.33%) and acceptable precision with relative standard deviation, RSD ≤ 5.54%. The results showed that magnetic solid RGO/Fe3O4 could be a suitable adsorbent in the preconcentration and extraction of TCAs in water samples.